Company valuation: objectives aspects in the verification of economic value of intangibles assets - Santos, Nivaldo João dos (2018)
This article discusses objective aspects in determining economic value to the intangible assets created by the company. Such assets, housed under the name of intellectual capital or goodwill, are represented by the brand, the good customer service and the prime location of business, among others. This is a case study of company and business valuation within the auto industry, located in southern Brazil, involving judicial determination. The methodological procedures involved the economic valuation of the company in two ways: a) as a set of equity assets and b) as a business generator of free cash flow over the years. It was shown that the refinement of information about the operating assets and the proper understanding of the relevant costs and expenses to particular business are essential for determining the fair value of the company and offers more objectivity to the calculation of the related economic value to the set of intangibles assets created.